Transcutaneous electrical nerve stimulation in management of neurogenic bladder secondary to spina bifida - Swapnil Pattanshetti; Jai Kumar Mahajan; Somya Saxena; Akshay Saxena (Wolters Kluwer Medknow Publications, 2022)
Aims: To assess the role of transcutaneous electrical nerve stimulation (TENS), alone or in combination with anticholinergic drugs in the management of neurogenic bladder (NB) in spina bifida (SB). Materials and Methods: All the consecutive patients, visiting outpatient clinic between July 2017 and December 2018, who were toilet trained and at least 1 year post-SB surgery with clinical and/or urodynamic evidence of NB, were included in the study. Out of 65 patients, 40 fulfilled the inclusion criteria and were randomised into: group A (ten patients, placebo TENS with anticholinergic agents), Group B (14 patients, TENS therapy with placebo medications) and Group C (16 patients, TENS therapy with anticholinergic medications). All the patients maintained a voiding diary and underwent assessment before and after the intervention. The study was approved by the Institutional Ethics Committee. Results: The presenting symptoms were urinary incontinence (100%), increased frequency (45%), straining during micturition (22.5%), urgency (22.5%), and hesitancy (30%). The demographic parameters were comparable in all the groups. After group specific intervention, the wet episodes/day significantly improved in Group C (P = 0.001). Similarly, the mean wet days/week also improved significantly in Group C (6.5-4.37 days/week, P = 0.01). Out of 40 patients, 29 had abnormal findings on ultrasonography before the start of the therapy. Following intervention, only two patients in Group C showed normalization of findings. On Urodynamic studies, detrusor pressure (Pdet max) decreased in all the groups; however, the patients in Group C, showed the maximum reduction (56.6 ± 11-30 ± 6.7 cm H2O). Similarly compliance (9.4 to 14.5 cm H2O, P = 0.02) and bladder capacity (68%-88% of EBC, P = 0.001) also improved significantly in Group C as compared to other 2 groups Overall, nine patients (Group A, B, and C = 1, 3, and five patients, respectively) showed detrusor instability, while post therapy, only one patient (Group B) had unstable bladder. Maximum decrease in postvoid residue (mean) was also observed in Group C (77-41 ml, P = 0.01). Conclusions: The application of TENS in NB secondary to SB is effective and its application led to improvement in symptoms, decrease in the wet episodes/day, maximum detrusor pressure, instability, bladder compliance, and capacity. TENS therapy in combination with anticholinergic agents had a better outcome as compared to monotherapy with either of the two modalities.